LongShengZhi Capsule Attenuates Alzheimer-Like Pathology in APP/PS1 Double Transgenic Mice by Reducing Neuronal Oxidative Stress and Inflammation - Yin, Zequn; Wang, Xuerui; Zheng, Shihong; Cao, Peichang; Chen, Yuanli; Yu, Maoyun; Liao, Chenzhong; Zhang, Zhongyuan; Han, Jihong; Duan, Yajun; Yang, Xiaoxiao; Zhang, Shuang (Frontiers in Aging Neuroscience, 2020)
Alzheimer’s disease (AD) is the most common dementia in the elderly, and may be caused by oxidative stress, inflammation and cerebrovascular dysfunctions in the brain. LongShengZhi Capsule (LSZ), a traditional Chinese medicine, has been approved by China Food and Drug Administration for treatment of patients with cardiovascular/cerebrovascular disease. It contains several neuroprotective ingredients including Hirudo, Astmgali Radix, Carthami Flos (Honghua), Persicae Semen (Taoren), Acori Tatarinowii Rhizoma (Shichangpu) and Acanthopanax Senticosus (Ciwujia). In this study, we aimed to determine the effect of LSZ on AD process. The amyloid-β precursor protein and mutant human presenilin 1 double transgenic (APP/PS1) mice at 2-month-old as the AD model were started LSZ treatment for 7 months. LSZ significantly improved the cognition of the mice without adverse effects, indicating its high safety and efficiency after a long-term treatment. LSZ reduced AD biomarker Aβ plaque accumulation by inhibiting β-secretase and γ-secretase expression. LSZ also reduced p-Tau expression, neuron apoptosis and inflammation in the brain. Consistently, in vitro, LSZ ethanol extract enhanced neurons viability by reducing L-glutamic acid-induced oxidative stress and inflammation in HT-22 cells. Mechanistically, LSZ exerted antioxidative effects by enhancing superoxide dismutase and glutathione peroxidase expression, reduced Ab accumulation by inhibiting presenilin 1 expression and p-Tau level by inhibiting NF-κB-mediated inflammation. It also demonstrated neuroprotection effects by regulating Fas cell surface death receptor/B-cell lymphoma 2/p53 pathway. Taken together, our study demonstrates the anti-oxidative stress/inflammation and neuroprotective effects of LSZ in AD-like pathological process, and suggests it could be a potential medicine for AD treatment.